Extra Robotic Thumb and Exoskeleton Robotic Fingers for Patient with Hand Function Disability - Rifky Ismail; Mochammad Ariyanto; Kharisma A. Pambudi; Joshua W. Syafei; Gilar P. Ananto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper presents the development of wearable robot to enhance and to assist people who lost the ability to grasp object. In the developing countries, most persons with hand disabilities still use manual and passive tools, especially for prosthetic and orthotic. We propose a wearable robot as an orthotic device namely extra robotic thumb and exoskeleton robotic fingers as new type of wearable robot for assisting person whose the thumb can not move anymore and the other four fingers has diminished fingers function. The motion of exoskeleton robotic finger has four DOF which each DOF represents the motion of flexion and extension on the fingers. For extra robotic thumb, it has two DOF to represent the motion of circumduction and flexion/extension on the thumb. The robot employs four linear actuators in exoskeleton robotic fingers and uses two micro servos in extra robotic thumb. The robot is designed based on 3D print technology. To assist person in Activity of Daily Living (ADL), five grip patterns are developed in this research. User can command the robot by using electromyography (EMG) sensor that attached on near healthy elbow. Based on the experimental results, the robot can successfully perform object grasping tasks by using the developed five grip modes.